Ural Airlines jet at the Pulkovo Airport St. Petersburg, Russia ... - Campbell, Sandy (University of Alberta Library, 2016)
This Airbus A321 passenger jet operated by Ural Airlines was parked at a jetway at Pulkovo Airport, St. Petersburg Russia. The cargo door is open and a baggage tractor pulling five baggage carts is alongside the train. ...